Spectral Analysis, Molecular Orbital Calculations and Antimicrobial Activity of PMF-G Fraction Extracted from PM-701 - ANWAR EL-SHAHAWY; NAGWA M ELSAWI; WADIAH SALEH BAKER; FATEN KHORSHID; NEVEEN S GEWEELY (International Journal of Pharma and Bio Sciences, 2010)
PM701 is a natural product and it is free of toxicity. The extracted fraction which coded PMF was found in 150 mg /g of lyophilized PM- 701 and it was able to inhibit significantly the proliferation of cancer cells without affecting the normal cells at cell culture level. The PMF-G fraction has been fractionated from PM-701 sample and it has been concluded that this fractionated sample has anti-carcinogenic effect on lung cancer and Leukemic cells. The elemental analysis, mass, infrared, atomic absorption and electronic spectra had been done for this sample and it has been concluded that the main constituent is amino acid and some salts. The structural studies were done by DFT method in the bases set B3LYP/6-31G** using Gaussian 98 to calculate the ionization energies, electron affinities and dipole moments in comparison to those of nucleic acid bases and AMP. The different values of low ionization energies and high electron affinities permit the electron transfer between these amino acids and the nucleic acid bases to excess or loss of an electron in the DNA of the human being cell. It has been concluded from the mass spectra that the major component of the G-fraction is cysteine and from the atomic absorption it has been concluded that it contains some elements mainly K, Na, Zn, , Fe, Cu, Br and Cl. The antimicrobial activities of the PM701 and pure fraction PMF were detected against four dermatophytic fungi ( Aspergillus fumigatus, Epidermophyton floccosum, Microsporum canis and Trichophyton rubrum), two Gram-positive bacteria (Staphylococcus citrus and Bacillus subtilis) and two Gram–negative bacteria (Escherchia coli and Salmonella typhi). The crude extract of camel urine showed the higher antimicrobial activity up to 32 mm inhibition zone with MIC < 100 µg/ml, compared with the low antimicrobial activity (< 10 mm inhibition zone) accompanied with MIC in the range of 100- 150 µg/ml of the pure extract of PM 701. The maximum toxicity (40-85 % cell mortality) was observed with addition of 100% crude extract of PM 701.